Progressive Reduction of its Expression in Rods Reveals Two Pools of Arrestin-1 in the Outer Segment with Different Roles in Photoresponse Recovery - Cleghorn, Whitney M. (Public Library of Science, 2011)
Light-induced rhodopsin signaling is turned off with sub-second kinetics by rhodopsin phosphorylation followed by arrestin-1 binding. To test the availability of the arrestin-1 pool in dark-adapted outer segment (OS) for rhodopsin shutoff, we measured photoresponse recovery rates of mice with arrestin-1 content in the OS of 2.5%, 5%, 60%, and 100% of wild type (WT) level by two-flash ERG with the first (desensitizing) flash at 160, 400, 1000, and 2500 photons/rod. The time of half recovery (t(half)) in WT retinas increases with the intensity of the initial flash, becoming ∼2.5-fold longer upon activation of 2500 than after 160 rhodopsins/rod. Mice with 60% and even 5% of WT arrestin-1 level recovered at WT rates. In contrast, the mice with 2.5% of WT arrestin-1 had a dramatically slower recovery than the other three lines, with the t(half) increasing ∼28 fold between 160 and 2500 rhodopsins/rod. Even after the dimmest flash, the rate of recovery of rods with 2.5% of normal arrestin-1 was two times slower than in other lines, indicating that arrestin-1 level in the OS between 100% and 5% of WT is sufficient for rapid recovery, whereas with lower arrestin-1 the rate of recovery dramatically decreases with increased light intensity. Thus, the OS has two distinct pools of arrestin-1: cytoplasmic and a separate pool comprising ∼2.5% that is not immediately available for rhodopsin quenching. The observed delay suggests that this pool is localized at the periphery, so that its diffusion across the OS rate-limits the recovery. The line with very low arrestin-1 expression is the first where rhodopsin inactivation was made rate-limiting by arrestin manipulation.